Differentiation of Toxoplasmosis and Lymphoma in AIDS Patients by Using Apparent Diffusion Coefficients - Camacho, Daniel L. A.; Smith, J. Keith; Castillo, Mauricio (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Distinguishing between toxoplasmosis and lymphoma brain lesions in AIDS patients is difficult but clinically relevant. This study was performed to test the hypothesis that diffusion-weighted (DW) imaging with apparent diffusion coefficient (ADC) maps can be used to distinguish these two lesions.METHODS: The ADC values were calculated in regions of interest placed in 13 brain toxoplasmosis lesions and eight brain lymphoma lesions in patients with AIDS. These values were compared with those of normal white matter. ADC ratios in lymphoma lesions then were compared with those in toxoplasmosis lesions by using a two-sample two-tailed t test.RESULTS: Toxoplasmosis lesions demonstrated significantly greater diffusion than that of lymphoma lesions (P = .004). ADC ratios were 1.63 ± 0.41 (mean ± standard deviation) in the 13 toxoplasmosis lesions and 1.14 ± 0.25 in the eight lymphoma lesions. While considerable overlap was present for ADC ratios between 1.0 and 1.6, ADC ratios greater than 1.6 were associated solely with toxoplasmosis, accounting for seven of 13 toxoplasmosis lesions.CONCLUSION: ADC values are helpful in differentiating toxoplasmosis from lymphoma in patients with AIDS.